“Memajukan UMKM di Ternate: Eksplorasi Peran Inklusi Keuangan dalam Menggabungkan Literasi dan Teknologi Finansial - Jeandry, Gregorius; Dara, Amin; Zainuddin, Zainuddin (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to examine the effect of Financial Literacy and Financial Technology on MSME Performance Improvement mediated by Financial Inclusion in Ternate City. This research uses a type of Quantitative Descriptive research and the nature of this research is explanatory research. The sample of this study is 100 MSMEs in Ternate City. The sampling technique uses purposive sampling method. The data analysis used is PLS (Partial Least Square) analysis with the help of Smart PLS. The results showed that financial literacy and financial technology affect the performance of MSMEs and financial inclusion is able to mediate the relationship between financial literacy, financial technology and MSME performance.